ISOLAMENTO E AVALIAÇÃO DE BACTÉRIAS DO GÊNERO BACILLUS COM POTENCIAL PARA USO EM BIOCIMENTAÇÃO NA PRODUÇÃO DE ARGAMASSAS - Almeida, Jupira; Thome, Antonio; Tonial, Fabiana; Siqueira, Gabriel do Nascimento (ENCONTRO NACIONAL DE TECNOLOGIA DO AMBIENTE CONSTRUÍDO, 2018)
This study had as aim to isolate bacteria of the genus Bacillus from soil samples, in order to carry out an investigation of its potential in the production of urease, so that it can be used in biocementation. From a clayish latossoil in the horizont B, a soil sample was extracted, diluted in saline solution and put through a temperature of 80ºC in order to separate only colonies of bacteria that produce urease. From the solution, a solid biomass was produced in which the colonies got sporulated. After that, the colonies were revitalized so they could be used in the manufacture of mortar. A pilot test was made utilizing the bacterias instead of cement in the mortar and after 28 days the specimen was tested in its compression and traction. The results did not reach the minimum of resistance established by the technical rules but pozzolanic activity could be observed because the sample with no bacterial use was 50% less resistent than the rest. Therefore, it is possible to replace other cement materials for urease production bacteria.